Application of Novel Drug Delivery System in Enhancing the Therapeutic Potential of Phytoconstituents - Singh, Dilpreet (Asian Journal of Pharmaceutics (AJP), 2015)
Various phytoconstituents obtained from nature have wide biological activities in chronic diseases and have wide therapeutic efficacy. The main advantage of using phytoconstituents is it provides free from adverse effects treatment where none of the medication can do. However, the physiochemical properties such as poor solubility, poor permeation, and non-targeting at the active site will create a barrier which hinders its therapeutic efficacy. So, various nanoformulation strategies are employed to overcome these barriers and provide uniform drug targeting at the active site in desired concentration and improved therapeutic efficacy. These strategies will constitute novel drug delivery systems (NDDS), such as nanoparticles, emulsion-based formulations, liposomes, phytosomes, microspheres, and topical based formulations, are available in commercial level to enhance the bioavailability of the poorly soluble herbal drug. In this review, we highlighted some novel applications of NDDS based approaches for enhancing the therapeutic potential of phytoconstituents having wide biological activities.